Mental retardation in a boy with an interstitial deletion at Xp22.3 involving STS, KAL1, and OA1: Implication for the MRX locus - Muroya, Koji; Ogata, Tsutomu; Matsuo, Nobutake; Nagai, Toshiro; Franco, Brunella; Ballabio, Andrea; Rappold, Gudrun; Sakura, Nobiro; Fukushima, Yoshimitsu (American journal of medical genetics, 1996)
Although genotype-phenotype correlations in male patients with various types of nullisomy for Xp22.3 have assigned a locus for X-linked mental retardation (MRX) to an approximately 3-Mb region between DXS31 and STS, the precise location has not been determined. In this paper, we describe a 14 7/12 year old Japanese boy with mental retardation and an interstitial deletion at Xp22.3 involving STS, KAL1, and OA1, and compare the deletion map with that of previously reported three familial male patients with low-normal intelligence and a similar interstitial deletion at Xp22.3. The results suggest that the MRX gene is further localized to the roughly 1.5-Mb region between DXS1060 and DXS1139. © 1996 Wiley-Liss, Inc.
Gesehen am 30.03.2021